Targeted treatments for dysfunctional uterine bleeding based on endometrial thickness - Htwe, Thi Thi; Yi, Hla Hla; Ku, Saw Kler (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Dysfunctional uterine bleeding is a common presentation to both general practitioner and gynaecologists which can have a significant effect on a woman’s quality of life. The aim of this study is to assess the effectiveness of treating dysfunctional uterine bleeding according to endometrial thickness. Methods: This study was a hospital based prospective study undertaken in gynecology outpatient clinic of Central Women’s Hospital, Mandalay, Myanmar for one-year period (2016). A total of 60 patients were recruited and divided into 3 groups based on endometrial thickness and offered targeted hormonal treatments. At the end of the one-month treatment, patients were asked to return for a follow-up visit and from their menstrual diaries, the number of bleeding days and bleeding scores were assessed and calculated. Results: Among sixty women with dysfunctional uterine bleeding, 55% of patients had endometrial thickness less than 6 mm, 25% had endometrial thickness 6-11 mm, with 20% of patients having endometrial thickness more than 11 mm. After one month of study period, treatment was found to be effective in 86.6% of the patients according to bleeding days and in 70% of the patients according to bleeding score. Conclusions: In women presenting with dysfunctional uterine bleeding, increased endometrial thickness was found to be associated with increased BMI. In the treatment of dysfunctional uterine bleeding, when the endometrial thickness of the patient was assessed and hormonal treatment was given according to the endometrial thickness, treatment was proven to be effective.